Implementasi Sistem Informasi Perpustakaan Untuk GBI Antiokhia Berbasis Web Menggunakan Framework Adonis JS Pada Node JS Menggunakan Metode Prototype - Christoval, Peter; Harahap, Syaiful Zuhri; Nasution, Marnis; Masrizal, Masrizal (Jurnal Pendidikan Indonesia, 2025)
Church libraries play a crucial role in supporting literacy and spiritual growth by providing various reading materials such as religious books, Bible references, and other supporting literature. However, manual library management still presents significant challenges, such as recording errors, book discrepancies, inaccurate fine calculations, and difficulty in accessing past reports, which hampers system efficiency. As the collection grows, the manual system becomes increasingly inefficient, prone to data loss, and cumbersome for information retrieval. Therefore, a web-based library management system is needed to automate the processes of collection management, book borrowing, and return, while ensuring data security and accuracy. This study aims to design and develop a web-based library information system for GBI Antiokhia, utilizing the AdonisJS technology stack, to address these challenges. The system is developed using the Prototyping method, ensuring user interaction and feedback throughout the development process. The system’s features include member data management, book management, borrowing and returning books, fine management, and report generation, all built to be efficient, secure, and user-friendly. This research also examines how the implemented system can solve the existing library management issues and improve operational effectiveness.